ADAPTATION TO COPE WITH THE PHENOMENON OF CORAL REEFS BLEACHING FOR CARRYING OUT SUSTAINABLE TOURISM - Sadikin, Pipin Noviati (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
The tourism sector is very sensitive to climate change. Especially for the tourism sector in Indonesia which relies heavily on natural resources and biodiversity, both in the waters or sea and mountains. The impact of climate change on the tourism sector can be immediately seen. Based on the background description above, this article will elaborate an overview of the influence of climate change and the potential impact on coral reef bleaching and its consequences on the tourism sector that may occur in Indonesia. This study aims to obtain the general portrait regarding the coral reef which may be affected by the climate change and the adaptation effort for oceanique tourism in Indonesia. The study uses a qualitative approach using library search. Supporting data and information were obtained from various literature in the form of books, reports, journals, magazines and relevant internet sites. Data is presented in the form of a narrative description and analyzed descriptively in accordance with the research objectives. The adaptation effort are (1) Maintain the health of the underwater ecosystem, (2) Involving Tourists in Bleaching Issues, (3) Diversify the tourism industry, (4) Reducing the Impact of Tourism Activities in General, (5) Encourage tourists to contribute funds to recovery and management efforts, (6) Disseminate Information to the Public Through Education and Other Propaganda. Meanwhile, for institutional capacity, adaptations can be made as follows: (1) Institutional Strengthening, (2) Community-Based and Collaborative Management, (3) Public Awareness, Education and Extensification.